Quality of work life among employees in TGS Maritime Technology Sdn Bhd / Hamdillah Ithnin & Nur Adillah Shaharum - Ithnin, Hamdillah (2019)
TGS Maritime Technology Sdn Bhd is the organization that offered the services and repairing in Marine Industry. As an employer, TGS Maritime has given its best in providing good perks and benefits to their employees. However, there are some issues that caused dissatisfaction among the employees and lead to decreasing in employee's quality of work life. Some issues such as heavy workload and no appropriate for resting. Quality of work life of employees is crucial in order to accomplish organization's mission and vision as well as producing good quality of work. Therefore, the objectives of this study are to analyze the factors that affect quality of work life among employees in TGS Maritime. This study employs both the quantitative and qualitative approach. The academic construct consist of SWOT and TOWS analysis. 34 questionnaires were distributed and returned by the staff of TGS Maritime Technology Sdn Bhd. It is found that workload has a strong negative relationship while compensation and benefit as well as working environment have weak positive relationships in affecting the quality of work life. Thus, it is recommended that in order to reduce the workload among employees, the management of TGS Maritime should employ more skilled employees, specialized in certain activities.